A comparative study of microRNAs in different stages of Eimeria tenella - Zhang, Lei; Chen, Linlin; Zhang, Hongtao; Si, Hongbin; Liu, Xianyong; Suo, Xun; Hu, Dandan (Frontiers in Veterinary Science, 2022)
Apicomplexan parasites have divergent biogenesis machinery for small RNA generation. Analysis has shown that parasites in Plasmodium and Cryptosporidium as well as many species in Leishmania or Trypanosoma do not have a complete machinery in small RNA biogenesis. Recently, the miRNA-generating system of Toxoplasma has been identified as plant/fungal-like and its miRNAome has been elucidated. However, the microRNA (miRNA) expression profiles and their potential regulatory functions in different stages of Eimeria tenella remain largely unknown. In this study, we characterized the RNA silencing machinery of E. tenella and investigated the miRNA population distribution at different life stages by high-throughput sequencing. We characterized the expression of miRNAs in the unsporulated oocyst, sporulated oocyst and schizogony stages, obtaining a total of 392 miRNAs. We identified 58 differentially expressed miRNAs between USO (unsporulated oocysts) and SO (sporulated oocysts) that were significantly enriched for their potential target genes in the regulation of gene expression and chromatin binding, suggesting an epigenetic modulation of sporulating by these miRNAs. In comparing miRNA expression at endogenous and exogenous developmental stages, twenty-four miRNAs were identified differently expressed. Those were mainly associated with the regulation of genes with protein kinase activity, suggesting control of protein phosphorylation. This is the first study about the evolution of miRNA biogenesis system and miRNA control of gene expression in Eimeria species. Our data may lead to functional insights into of the regulation of gene expression during parasite life cycle in apicomplexan parasites.